Performance evaluation of the Bhakra Irrigation System, India, using remote sensing and GIS techniques - Sakthivadivel, Ramaswamy; Thiruvengadachari, S.; Amarasinghe, Upali A.; Bastiaanssen, Wim G.M.; Molden, David J. (International Water Management Institute, 1999)
Describes the use of satellite remote sensing and GIs techniques to analyze the agricultural performance and sustainability of the Bhakra Irrigation System in India. Demonstrates the cost-effectiveness of these techniques as diagnostic tools for irrigation system improvement and the advantages of using SRS and GIs in combination.